2023
DOI: 10.3390/atmos14050871
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Precipitation Trends and Associated Large-Scale Teleconnections in Northern Pakistan

Abstract: The effects of climate change are unparalleled in magnitude, ranging from changing weather patterns that endanger food production to increasing sea levels that increase the likelihood of catastrophic flooding. Therefore, determining the extent of such variations on regional and local scales is imperative. We used monthly precipitation data from 25 meteorological stations in northern Pakistan (NP) to document the observed changes in seasonal and annual precipitation. The station density in the NP is small and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 95 publications
(129 reference statements)
2
10
0
Order By: Relevance
“…The same is evident for the ENSO4.0 but the dipole pattern shows a regionally varying effect. The mechanism of the dipole pattern for the eastern Pacific and UTCI min could be related to the ENSO-driven monsoon circulation that affects the South Asian monsoon through controlling the zonal easterlies and hence a negative relationship with the eastern parts of AP and positive relationship with the western AP 72 , 73 , 94 , 95 . The eastern Pacific on the other hand appeared to have widespread global effects and thus its positive mode could affect the Indian Ocean basin-wide forcing and the overall thermal stress regime of the AP region 96 99 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same is evident for the ENSO4.0 but the dipole pattern shows a regionally varying effect. The mechanism of the dipole pattern for the eastern Pacific and UTCI min could be related to the ENSO-driven monsoon circulation that affects the South Asian monsoon through controlling the zonal easterlies and hence a negative relationship with the eastern parts of AP and positive relationship with the western AP 72 , 73 , 94 , 95 . The eastern Pacific on the other hand appeared to have widespread global effects and thus its positive mode could affect the Indian Ocean basin-wide forcing and the overall thermal stress regime of the AP region 96 99 .…”
Section: Discussionmentioning
confidence: 99%
“…We preferred these non-parametric tests over other statistical tests as they are simple and robust against outliers and missing values in a time series 70 , 71 . Furthermore, these tests are less sensitive to abrupt breaks in a time series and do not require data normalization 72 , 73 . More details about SSE and m-MK tests can be found in recent studies 74 , 75 .…”
Section: Methodsmentioning
confidence: 99%
“…El Niño, the warm phase of ENSO, is associated with enhanced precipitation over South Asia, whereas La Niña, the cold phase, is associated with suppressed precipitation and drought (Barlow et al 2021). For instance, Rebi et al (2023) and Nawaz et al (2023) observed dominant interannual precipitation coherences in northern Pakistan. The population in southern Pakistan is highly dependent on agriculture to meet basic livelihood needs.…”
Section: Discussionmentioning
confidence: 99%
“…Like, the stations were selected based on data length, completeness, and quality (i.e. consistency and homogeneity), and deviations attributed to climatic and non-climatic factors were checked (Kidd et al 2017, Ullah et al 2021, Hussain et al 2022a, 2022c, Rebi et al 2023. As, it is important to guarantee that observed temperature trends must represent natural variability instead of non-climatic factors, such as heat islands (El Kenawy et al 2012, Hussain et al 2023b.…”
Section: Datamentioning
confidence: 99%
“…The ERA5 dataset, which has a horizontal spatial resolution of 30 km, combines extensive past climate observations into global‐scale approximations using advanced modelling techniques and data integration methods (Ali et al, 2022; Mistry et al, 2022). Due to the lack of long‐term observational data from various weather stations across Pakistan, the ERA5 dataset was chosen for this region due to its higher resolution and availability over an extended period (Rebi et al, 2023; Waseem et al, 2022; Zittis et al, 2016). Compared to other products, this ERA5 reanalysis product performed well in reproducing climate variables such as precipitation and temperature in the region (Ali et al, 2022; Waseem et al, 2022).…”
Section: Datasetsmentioning
confidence: 99%